Implementasi dan modifikasi WebShell untuk monitoring serangan berbasis website: WebShell Implementation And Modification For Website-Based Attack Monitoring - Dian Widiyanto Chandra; Paulus Miki Resa Gumilang (AITI, 2021)
Backdoor is code commonly used by hackers to gain access to a web page illegally, backdoor or commonly called a web shell is currently used by hackers to attack a web page, but in handling attacks that use a web shell. not always detectable quickly it even takes months to realize a web page has embedded a web shell. To deal with this problem, we need an application that can quickly detect attacks carried out by embedding a web shell on a web page. The purpose of this research is to modify the existing web shell so that it can be monitored when it is used by hackers to attack a website. The monitoring process is carried out using a web page created by the author. The results of the discussion of this study are expected to reduce losses arising from attacks carried out by hackers using a web shell.